The sodium‐glucose co‐transporter 2 inhibitor tofogliflozin suppresses atherosclerosis through glucose lowering in ApoE‐deficient mice with streptozotocin‐induced diabetes - Masahiko Iwamoto; Tetsuya Kubota; Yoshitaka Sakurai; Nobuhiro Wada; Seiji Shioda; Toshimasa Yamauchi; Takashi Kadowaki; Naoto Kubota (Wiley, 2022)
Abstract Epidemiological and animal studies have revealed that sodium‐glucose cotransporter 2 (SGLT2) inhibitors suppress cardiovascular events in subjects with type 2 diabetes and atherosclerosis in animal models of diabetes. However, it still remains unclear if the anti‐atherosclerotic effect of SGLT2 inhibitors is entirely dependent on their glucose‐lowering effect. Tofogliflozin, a highly specific SGLT2 inhibitor, was administrated to apolipoprotein‐E‐deficient (ApoEKO) with streptozotocin (STZ)‐induced diabetes and nondiabetic ApoEKO mice. After 6 weeks, samples were collected to investigate the histological changes and peritoneal macrophage inflammatory cytokine levels. Tofogliflozin suppressed atherosclerosis in the diabetic ApoEKO mice. The atherosclerosis lesion areas and accumulation of macrophages in these areas were reduced by tofogliflozin treatment. The expression levels of interleukin (IL)‐1β and IL‐6 in the peritoneal macrophages were significantly suppressed in the tofogliflozin‐treated diabetic ApoEKO mice. Tofogliflozin treatment failed to inhibit atherosclerosis in the nondiabetic ApoEKO mice. No significant difference in the anti‐atherosclerotic effects of insulin and tofogliflozin was observed between diabetic ApoEKO mice with equivalent degrees of glycemic control achieved with the two treatments. Insulin treatment significantly reduced the IL‐1β and IL‐6 expression levels in the peritoneal macrophages of the diabetic ApoEKO mice. Significant decrease of the LPS‐stimulated IL‐1β concentrations was also observed in the conditioned medium of the peritoneal macrophages collected from insulin‐ and tofogliflozin‐treated diabetic ApoEKO mice. These results suggest that tofogliflozin suppresses atherosclerosis by improving glucose intolerance associated with inhibition of inflammation. Tofogliflozin suppresses atherosclerosis in ApoEKO mice with STZ‐induced diabetes via its glucose‐lowering effect.